Performance of District Forums in Tamil Nadu: A Statistical Comparative Report - Yamuna Krishna, B.; Suganya, Y. (Prabandhan: Indian Journal of Management, 2013)
Consumerism in India is still in its nascent stages, even though India has celebrated the silver jubilee (25 years) of the enactment of the Consumer Protection Act (CPA), 1986. 80.33% (2011 census) of the population of Tamil Nadu is literate, but a majority of the population is unaware about the Act, their rights and duties, and about the functioning of the consumer courts at National, State, and District Levels. The present study examines and compares the performance of all 30 District Forums in Tamil Nadu for a period of 4 years commencing from January 2007 to December 2010 (2007, 2008, 2009, and 2010). District Forums were studied 'Collectively' and not 'Individually'. 'Monthly Statement of Pending and Disposal' (48 monthly statements) on the Number of cases pending at the beginning of each month, Cases filed in each month, Total cases to be disposed off in each month, Disposed in each month, and Pending cases at the end of each month were obtained from the Tamil Nadu State Commission, and was used as the base data. The study excludes cases under Non-Appearance, Technical Grounds, and Against Government. Statistics revealed that, on an average, all the 30 District Forums in Tamil Nadu had disposed off only 4.59% of the cases and about 95.39% of the cases were pending during the years 2007, 2008, 2009, and 2010. Statistics conclude that District Forums in Tamil Nadu functioned inefficiently during the study period. However, this conclusion will be one-sided if 100% blame is imposed on the Government, as 50% of the blame also falls on the consumers themselves. Consumers, rather than demanding the streamlining of the existing condition and disposing off the backlog of cases in consumer courts, have to make optimum use of the dysfunctional courts to fight against unethical trade practices.